2019
DOI: 10.1101/684811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early removal of senescent cells protects retinal ganglion cells loss in experimental ocular hypertension

Abstract: Experimental ocular hypertension induces senescence of retinal ganglion cells (RGCs) that mimics events occurring in human glaucoma. Senescence‐related chromatin remodeling leads to profound transcriptional changes including the upregulation of a subset of genes that encode multiple proteins collectively referred to as the senescence‐associated secretory phenotype (SASP). Emerging evidence suggests that the presence of these proinflammatory and matrix‐degrading molecules has deleterious effects in a variety of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The data that support the findings of this study are openly available in GEO database (GSE141725) and in Dryad at https://doi.org/10.6075/J0707ZTM (Rocha, ).…”
Section: Data Availability Statementsupporting
confidence: 69%
“…The data that support the findings of this study are openly available in GEO database (GSE141725) and in Dryad at https://doi.org/10.6075/J0707ZTM (Rocha, ).…”
Section: Data Availability Statementsupporting
confidence: 69%
“…Interestingly, the core genes within significantly enriched pathways (e.g., inflammatory and apoptosis) were robustly upregulated in 18-month-old animals upon stress whereas only slightly upregulated in young retinas (Figure 2H, Supplementary Figure 2K). Similarly, when we plotted heatmaps for senescence and extracellular matrix deregulation pathways 18 we have observed robust upregulation of the genes in these pathways in 18-month-old IOP-treated retinas but only limited deregulation in 3-monthold-treated retinas. In total, out of 65 top genes dysregulated upon IOP-elevation in 18-month-old retinas, 53 were upregulated more in the old retinas than in the young retinas upon IOP stress (Supplementary Figure 2M).…”
Section: Aged Retina Is More Sensitive To Mild Intraocular Pressure E...mentioning
confidence: 76%
“…In our previous works we have demonstrated that intraocular hypertension of 90 mmHg, non-physiological levels of pressure, induced ∼50% loss of RGCs. 11,18 Therefore, in search of a better system that would mimic the glaucomatous insult, the effects of different levels of IOP elevation on RGC survival were quantified, by unilaterally elevating IOP in 3-month-old C57BL/6J to 30, 50, or 90 mmHg for 1 hour. The contralateral eye served as a healthy sham control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common chronic neurodegenerative diseases in humans is glaucoma, which is a leading cause of irreversible blindness worldwide. Although a study in a mouse model showed that dasatinib prevented glaucoma-dependent loss of retinal functions and cellular structure, 41 a retrospective study assessing the effects of senolytic drugs on vision in 28 patients with glaucoma showed that senolytic exposure did not affect visual acuity or intraocular pressure, and did not have toxic effects. 74 This pilot study implies that senolytic drugs might not have clinically significant toxicity and, therefore, could be safe for use in humans.…”
Section: Effects Of Senotherapeutics On the Nervous Systemmentioning
confidence: 99%